Educational lessons from the past – marketing textbooks during the Age of Enlightenment (16th to 18th Centuries). (17th August 2015) - Shaw, Eric
Abstract : Purpose: – The purpose of this paper is to critique four marketing textbooks written during the Age of Enlightenment (sixteenth-eighteenth centuries) to understand the educational lessons they taught students of marketing at the time and the lessons they might hold for the present day. Design/methodology/approach: – The method entails critically examining several marketing textbooks within the context of the great social, religious, intellectual, political and economic changes taking place at the time. Findings: – Over the period, paralleling developments in the Enlightenment, the two earlier textbooks of the age have a heavier emphasis on religious and ethical concerns along with their discussions of business issues. The two later textbooks de-emphasize spiritual themes in favor of almost completely focusing on business matters. In addition to discussing themes relevant to their times, the books anticipate concepts found in marketing textbooks of today. Generally, there is also more stress placed on immediate facts rather than enduring business principles. Yet many principles are discussed, including the most fundamental and durable principle of merchandising: "buy cheape, sell deare". Originality/value: – There is no other review of a collection of marketing textbooks during the Age of Enlightenment in the published literature.